2019
DOI: 10.3390/electronics8060694
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Residue Number System Using Hardware Efficient Diagonal Function

Abstract: The residue number system (RNS) is a non-positional number system that allows one to perform addition and multiplication operations fast and in parallel. However, because the RNS is a non-positional number system, magnitude comparison of numbers in RNS form is impossible, so a division operation and an operation of reverse conversion into a positional form containing magnitude comparison operations are impossible too. Therefore, RNS has disadvantages in that some operations in RNS, such as reverse conversion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
(62 reference statements)
1
14
0
1
Order By: Relevance
“…It was observed that diagonal modulus of special binary representations (very low or very high Hamming weight) are useful in the construction of RNS with good performance. This point was described in [7].…”
Section: Rns Math Background Methodologymentioning
confidence: 87%
See 4 more Smart Citations
“…It was observed that diagonal modulus of special binary representations (very low or very high Hamming weight) are useful in the construction of RNS with good performance. This point was described in [7].…”
Section: Rns Math Background Methodologymentioning
confidence: 87%
“…Example. Consider quadruples (43, 51, 79, 91), (23, 43, 87, 143), (5,29,93,313) and (3,7,43,2323) however, in practice preference should be given to the quadruple (43, 51, 79, 91), since it is very well balanced, which is confirmed by the smallest value .…”
Section: Balance Metric For Building Effective Computational Systemsmentioning
confidence: 99%
See 3 more Smart Citations